E-032 Imaging characteristics of tumors of the head and neck. (4th July 2012) - Hardman, J; Kato, C; Rezai, P; Kumar, G
Abstract : Purpose: Tumors of the head and neck have characteristic findings on MRI and cerebral angiography which help with proper diagnosis and localization. This presentation will provide a review of the characteristic findings of tumors commonly found in the head and neck. Materials and Methods: A retrospective analysis was made of head and neck tumor cases for the past 10 years from the PACS system at Cook County Hospital. All selected cases are biopsy proven. Results: We compare and contrast the characteristic MRI and cerebral angiogram findings of glomus jugulare tumors, glomus vagale tumors, carotid body tumors, meningiomas, schwannomas, paragangliomas, central neurocytoma, orbital tumors and metastatic tumors. All of these tumors have typical locations and vascular patterns observed on MRI and cerebral angiography. Conclusion: It is important to carefully analyze the imaging characteristics of tumors of the head and neck as this information will differentiate common tumors from the more complex ones. Each of these tumors have specific findings that use of MR and cerebral angiography, along with patient history, can help to determine further management. This review aims to refresh to the knowledge base of the neurointervenionalist in differentiating between these tumors. Competing interests: None.